1996
DOI: 10.1021/es960132l
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Characterization of IHSS Humic Substances:  Total Luminescence Spectra with Absorbance Correction

Abstract: Total luminescence spectroscopy was applied to the fluorescence characterization of humic substances obtained from the International Humic Substances Society (IHSS). Results show that total luminescence spectra, represented as excitation−emission matrices (EEMs), may be used to discriminate between soil-derived and aquatic-derived IHSS humic substances and between humic and fulvic acids derived from the same source (soil or aquatic). Ionic strength in the range of 0−1 M KCl and humic substance concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
218
0
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(241 citation statements)
references
References 11 publications
13
218
0
7
Order By: Relevance
“…This technique has satisfactorily been used to characterize DOM in natural environments. Although the EEM spectroscopic approach has a greater density of spectral information than the traditional fluorescence approaches, it can demonstrate that quenching (or enhancement) of fluorescence intensity by proton and metal ions is quantitatively dissimilar in different regions of the fluorescence landscape [2,[17][18][19][20][21]. The EEM landscape has been typically characterized by noting the locations of one or more peaks that correspond to the maximum fluorescence intensities ("peak picking") [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This technique has satisfactorily been used to characterize DOM in natural environments. Although the EEM spectroscopic approach has a greater density of spectral information than the traditional fluorescence approaches, it can demonstrate that quenching (or enhancement) of fluorescence intensity by proton and metal ions is quantitatively dissimilar in different regions of the fluorescence landscape [2,[17][18][19][20][21]. The EEM landscape has been typically characterized by noting the locations of one or more peaks that correspond to the maximum fluorescence intensities ("peak picking") [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence in natural waters is predominantly generated by organic and amino acids, which derive from decomposed plant and animal material in the soil zone. Several studies have investigated the fluorescence of these materials in soils, rivers, groundwater, and marine waters [Senesi et al, 1991;Coble, 1996;Mobed et al, 1996; A. Baker and D. Genty, Fluorescence wavelength and intensity variations of cave waters, submitted to Journal of Hydrology, 1998.] These studies have revealed the presence of several intensity peaks in the fluorescence spectrum but with a predominant organic acid peak in soil extracts and terrestrial waters at an excitation and emission wavelength pair of 290-350:400-480 nm, ascribed to a probable fulvic acid source.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional fluorescence spectroscopy (3DEEM) is a popular method in the component identification of CDOM and algae for its high sensitivity and small interference (Mobed et al, 1996;McKnight et al, 2001;Patel-Sorrentino et al, 2002;Leenheer and Croué, 2003;Murphy et al, 2008). With the development of fluorescence sensor, fluorescence-to-absorption algorithms to retrieve CDOM absorption became more and more significative.…”
Section: Introductionmentioning
confidence: 99%